2015
DOI: 10.1155/2015/375278
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Profunda Femoris Artery Aneurysms: Five Case Reports

Abstract: Profunda femoris artery aneurysm (PFAA) is an extremely rare entity, with most cases being asymptomatic, which makes obtaining an early diagnosis difficult. We herein report a case series of PFAA, in which more than half of the PFAAs, which presented with no clinical symptoms, were discovered incidentally. All PFAAs were treated surgically with aneurysmectomy with or without vascular reconstruction. In cases involving a patent superficial femoral artery (SFA), graft replacement of the profunda femoris artery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Femoral artery pseudoaneurysm has been well-documented in the literature following hip replacement surgery. [6] However, on intraoperative examination, the aneurysm was found to be a true aneurysm. A non-ruptured aneurysm would maintain all layers of the arterial wall, which was what was encountered during surgery, at least macroscopically.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Femoral artery pseudoaneurysm has been well-documented in the literature following hip replacement surgery. [6] However, on intraoperative examination, the aneurysm was found to be a true aneurysm. A non-ruptured aneurysm would maintain all layers of the arterial wall, which was what was encountered during surgery, at least macroscopically.…”
Section: Discussionmentioning
confidence: 96%
“…However, higher thresholds for intervention were advocated by other authors. [6] Lawrence et al [7] suggested a 3.5-cm threshold for repair of pooled femoral artery aneurysms. However, in their study, most of the patients had CFA or superficial femoral artery aneurysms and, therefore, the results should be viewed cautiously in case of PFAAs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that if the ipsilateral femoropopliteal lesion is patent without stenosis, the ligation may be sufficient [ 4 , 8 , 9 ]. However, Igari et al argued that PFAA should be treated with both aneurysmectomy and vascular reconstruction to preserve the PFA blood flow, which may positively affect future limb salvage [ 10 ]. We agree that reconstruction should be performed if the general condition is good.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 3 True aneurysms of the PFA are usually asymptomatic, but can present as a painful pulsatile groin mass. 2 , 4 , 5 Due to the nonspecific nature of the presenting symptoms, diagnosis is often delayed. Physicians need to have a high index of suspicion to prevent complications, which can include compression of surrounding structures, distal embolization, and rupture.…”
mentioning
confidence: 99%